Virtual building visualisation: a system development framework - Faisal Mohamed, Nur Fadziana; Mat Yamin, Fadhilah; Zulkifli, Abdul Nasir; Salleh, Mohd Jaafar (2005)
Building visualisation based on orthographic drawings has been used as a communication medium for architects to explain their ideas to their clients. Architects are well known to be proficient in three dimensional(30 visualisation from two dimensional(20) maps. Clients generally are not. The implication of unsatisfied presentation is that it will cause poor communication between the architects and their clients which will normally ends up with client lost. In this paper, a framework in developing a virtual building visualisation system is presented. It discusses the possibilities of applying CAD and 30 game engine in the creation of virtual environment (VE) jor building visualisations. The approach in the creation of 3D building model in AutoCADTMa and the integration of the model into the VE in UnrealyTM is also investigated. Finally, this paper discusses on the practical and technical issues cropped up during /he development process. The virtual building system is a viable solution for architects and designers in providing a cheaper, reliable and effective tool for visualisation and evaluation of building design. The integration of CAD and game engine also proves that a common database could be created and shared between the two applications which minimises data loss and ensures data compatibility between them.